Improving Teachers’ Capacities and Skills in Rwanda-An Evidence-Based Policy Proposal - NSHIMIYIMANA Alphonse (Researchparks Publishing, 2022)
The present article aimed at developing an evidence-based policy for professional and skills development of Teachers in Rwanda Basic Education System. It highlighted the need and the relevance as the Government is striving for an effective and quality teaching and learning system. The article shed light on key concepts and policy requirements to achieve the national and global aspirations in education and human capital development. The policy proposal grounded on key theoretical frameworks as well as both national and global educational and developmental contexts. The article demonstrated a need for teachers’ capacity building, continuous professional development for an optimum quality education mechanism and educational output.